Experimental and Numerical Analysis on the Damage and Failure Characteristics of Bituminous Coal under Multilevel Cyclic Loads. (7th April 2022) - Gong, Shuang; Wang, Chaofei; Zhou, Lei; Xi, Furui; Yao, Shibin; Li, Xiaojun; Liu, Juan; Wang, Wen
Abstract : The coal mining process is often accompanied by periodic disturbance of the surrounding rock mass around the coal mining face. Therefore, it is of great theoretical and engineering value to investigate the damage pattern of bituminous coal under cyclic loading and unloading conditions and analyze its damage precursors. The experiments of uniaxial multistage cyclic loading and unloading of bituminous coal were carried out, and the loading and unloading response ratios were extracted using the elastic modulus variation to describe the damage characteristics and damage precursors of bituminous coal. Based on the accumulated acoustic emission ringing counts, the response ratios were defined, and the internal damage evolution characteristics and damage laws during the damage of bituminous coal were analyzed. The CT scan images of the internal structure of the coal sample before and after the experiment were used to analyze the damage characteristics of the coal sample and the influence of the number of simulation units on the results using the inverse modeling simulation analysis method. The research shows that the response ratio of bituminous coal under uniaxial cyclic loading has three stages of variation, and it is characterized by periodic "W"-type variation at each level of stress. In addition, the inverse modeling and simulation can better characterize the damage evolution of the coal specimen.